The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1515/opag-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture for Space: People and Places Paving the Way

Abstract: Agricultural systems for space have been discussed since the works of Tsiolkovsky in the early 20

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 161 publications
0
91
0
2
Order By: Relevance
“…It has been suggested that, given its low energy consumption, LED technology could potentially be adopted in large-scale indoor farming [17], however, the feasibility of its use in small-scale indoor cultivation systems depended on the combined effect of several factors. The estimation of the energy input absorbed for each cycle gave quite a clear idea about how slight variation in the growing conditions (cycle length, photoperiod, light quality, and intensity) could impact on the final costs of the production, especially in small-scale systems, like those designed for indoor micro-growing.…”
Section: Effect Of Different Growing Conditions On Biomass Accumulatimentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that, given its low energy consumption, LED technology could potentially be adopted in large-scale indoor farming [17], however, the feasibility of its use in small-scale indoor cultivation systems depended on the combined effect of several factors. The estimation of the energy input absorbed for each cycle gave quite a clear idea about how slight variation in the growing conditions (cycle length, photoperiod, light quality, and intensity) could impact on the final costs of the production, especially in small-scale systems, like those designed for indoor micro-growing.…”
Section: Effect Of Different Growing Conditions On Biomass Accumulatimentioning
confidence: 99%
“…Interest in the use of LED lights and indoor cultivation systems is growing, as well as the concern about the environmental impact, the energy costs, and the quality of the produce that can be obtained [1,17]. It is generally thought that this kind of system cannot economically compete with traditional greenhouse cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…). European Space Agency initiated its Micro‐Ecological Life Support System Alternative (MELiSSA) project to test life support concepts based on ecological principles for materials cycling (Hendrickx and Mergeay , Wheeler ).…”
Section: Extremophile Microalgae In the Context Of Astrobiologymentioning
confidence: 99%
“…). Furthermore, such plants or platforms may be also supporting missions to Mars in the context of “space agriculture”(Wheeler ).…”
Section: Extremophile Microalgae In the Context Of Astrobiologymentioning
confidence: 99%
“…Nevertheless, algae, particularly microalgae, belong to a species that can be of great interest for vertical farming, e.g. for vertical agriculture in space [30], while the outdoor cultivation of temperature-tolerant algae such as Chlorella sorokiniana in column photobioreactors may also be a research objective aimed at sustainable food production [31]. Th is suggests that there is a broad area of research of possible new fi ndings and developments related to the growth of adherent algae on diverse textile fabrics with potential vertical farming applications.…”
Section: Textile Fabrics For Algae Immobilisation and Harvestingmentioning
confidence: 99%